User emotional responses and perceived quality characteristics for sustainable product design - Mohd Rashid, Mohamad Saiful Sazwan (2018)
Physical characteristic of products has a reflective significance in way the products are perceived. The design of a product regulates user’s first impression when they communicate with the product. It has been seen equally as function criteria that able to determine the product personality and becomes a significant factor for a product to sustain and also, bring emotional responses to user. Emotional responses are important in product interaction that provides a strong influence between user’s behavior and product attachment. Apart from emotions, perceived quality also contribute to evaluation regarding the product quality to meet individual’s expectations. It refers to indirect intention among product features and user’s orientation during decision-making process, helping the user to receive information about the product specifications. Nowadays, designers struggle to integrate a potential meaning to combine user’s emotional attachment with good product characteristics. They need to employ appropriate method in order to obtain user’s favorite product and establish the sustainable product. The purpose of this research is to develop a sustainable product design method that incorporate the user emotional responses, perceived quality characteristics and elements of sustainability as a design guideline in the early stage of product development process. A survey was conducted involving design experts and end users. The results show various variables were identified such sustainable product specification, perceived quality characteristics and element of sustainable product design. These fundamentals are contributed towards sustainable and successful product in the market.